Metal-Free Synthesis of Trifluoromethyl Carbinol-Containing Imidazo[1,2-a]pyridines via Dehydrative Coupling of Imidazo[1,2-a]pyridines with Trifluoroacetaldehyde - Liu, Zhaowen; Guo, Xiaohua; Chen, Zhixi; Wu, Longhui; Yang, Kai (Synthesis, 2024)
A facile and efficient method for the synthesis of trifluoromethylated carbinols has been developed from imidazo[1,2-a]pyridines and trifluoroacetaldehyde. The direct C(sp2)–H hydroxytrifluoromethylation is successfully implemented at room temperature using HFIP as solvent through dehydrative cross-coupling process, which displays a broad substrate scope and functional group tolerance. Furthermore, gram-scale and synthetic transformation experiments have also been demonstrated, which indicate its potential applicable values in organic synthesis. This green protocol features operational simplicity, atom economy, mild reaction conditions (e.g., at room temperature, transition-metal- and oxidant-free, without inert gas protection), wide substrate scope, and excellent practicality.
Keywords: imidazo[1,2-a]pyridines; trifluoromethylated carbinols; dehydrative cross-coupling; HFIP; metal-free